Adsorption on Heterogeneous Surfaces with Simple Topographies - P.M. Centres; F. Bulnes; J.L. Riccardo; A.J. Ramirez-Pastor; M.A. Perarnau (Adsorption Science & Technology)
The localized monolayer adsorption of interacting particles onto heterogeneous surfaces has been studied through Monte Carlo simulation in the framework of the lattice–gas model. The substrate was modelled as a collection of finite homotatic patches, each one characterized by an adsorption energy arising from a discrete energy density function. Patches were distributed spatially, either in a deterministic alternate way (ordered topography) or in a non-overlapping random way (random topography). The adsorption process was analyzed by following the behaviour of surface coverage versus chemical potential (adsorption isotherm) and the differential heat of adsorption as a function of the coverage. These quantities depend on the size of the patch as well as on the topological distribution of the patches on the surface. The consequences of these findings are discussed for the determination of the energetic topography of the surface from adsorption measurements.